Sistem Pendukung Keputusan Rantai Pasok Koperasi Pengolahan Susu X Di Jawa Barat - Rina Fitriana; Taufik Djatna (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2011)
A decision support system is a computerized information system, designed to support business and organizational decision-making activities. Agroindustrial Supply Chain Management (Agro-SCM) is the management of the entire set of production, transformation/processing, distribution and marketing activities in agroindustry by which a consumer is supplied with a desired product. Milk Processing Cooperation has a strategic role to support the milk industry development in Indonesia. The purpose of this research is to make a proposal supply chain decision support system of Milk Processing Cooperative X in West Java. The first sub model is Sales and Purchase. The second sub model is a Quality Risk. Third sub model is the Forecasting. The fourth sub model is Transportation. The Fift sub model is Supply Chain Management. Validation and Verification of Decison Support System conducted through case studies with empirical data in Milk Processing Cooperative X in West Java